Peran Angkutan Laut dalam Meningkatkan Distribusi Ternak Sapi Potong dari Daerah Produsen ke Wilayah Konsumen - Winarso, Bambang (Jurnal Penelitian Pertanian Terapan, 2014)
Nationally, there are some areas of the provinces in Indonesia is livestock center including East Nusa Tenggara province. East Nusa Tenggara Governor Decree No. 278/Kep/HK/2011 Deciding that the allocation of large livestock beef to local consumers (West Java, Jakarta and Kalimantan) each of (a) as 55.000 heads of cattle,(b) 7.000 buffalo and (c) 5.000 horse. For transporting live cattle the only means of transportation by ship. Darmaga Tenau in serving the transport of life cattle is still in a simple way. Similarly, in a transit Kalimas. In an effort to decrease the cattle of the ship had been taken in three ways: (a) transported and unloaded from boats using nets, (b) direct the cows are herded through the bridge and (c) using containers. However, in connection with a number of criticisms relating to the principle Animal welfare, inevitably a third pattern to be implemented despite the fact that take a long time and ultimately costs more mahal. This paper is part of the research results of ?Efisiensi Moda Transportasi Ternak dan Daging Sapi Dalam Mendukung Program Swasembada Pangan? by the Center for Economic and Agricultural Policy, 2013. Location of the study focused on East Nusa Tenggara and East Java. Keywords: marine transportation, livestock, distribution